An exploration of social determinants of health amongst internally displaced persons in northern Uganda - Roberts, Bayard (BioMed Central, 2009)
Social determinants of health describe the conditions in which people are born, grow, live, work and age and their influence on health. These circumstances are shaped by the distribution of money, power and resources at global, national and local levels, which are themselves influenced by policy choices. Armed conflict and forced displacement are important influences on the social determinants of health. There is limited evidence on the social determinants of health of internally displaced persons (IDPs) who have been forced from their homes due to armed conflict but remain within the borders of their country. The aim of this study was to explore the social determinants of overall physical and mental health of IDPs, including the response strategies used by IDPs to support their health needs. Northern Uganda was chosen as a case-study, and 21 face-to-face semi-structured interviews with IDPs were conducted in fifteen IDP camps between November and December 2006. The findings indicated a number of key social determinants. Experiencing traumatic events could cause "over thinking" which in turn could lead to "madness" and physical ailments. Respondents also attributed "over thinking" to the spirit (cen) of a killed person returning to disturb its killer. Other social determinants included overcrowding which affected physical health and contributed to an emotional sense of loss of freedom; and poverty and loss of land which affected physical health from lack of food and income, and mental health because of worry and uncertainty. Respondents also commented on how the conflict and displacement and led to changes in social and cultural norms such as increased "adultery", "defilement", and "thieving". Response strategies included a combination of biopsychosocial health services, traditional practices, religion, family and friends, and isolating. This study supports work exploring the political, environmental, economic, and socio-cultural determinants of health of IDPs. Addressing these determinants is essential to fundamentally improving the overall physical and mental health of IDPs.